Membranous nephropathy and cancer in the era of PLA2R testing. Issue 2 (June 2018) - Khairallah, Pascale; Bomback, Andrew
Membranous nephropathy has historically been associated with a higher risk of malignancy compared to the general population. Following a membranous nephropathy diagnosis, physicians screen patients for underlying cancers at the time of and up to several years following the diagnosis. The discovery of phospholipase A2 receptor (PLA2 R) as a major antigen in primary membranous nephropathy may be changing how we think about the association between membranous nephropathy and cancer. PLA2 R was found to be present in 72% of cases of idiopathic membranous nephropathy with very few PLA2 R patients having cancer. Following PLA2 R discovery, thrombospondin type-1 domain-containing 7A (THSD7A) was discovered. This antigen, in contrast to PLA2 R, may be more strongly associated with cancer. This review will evaluate the associations between these antigens and cancer, as well as propose an algorithm on cancer screening in the era of antibody testing.